Long-Term Memory Recursive Least Squares Online Identification of Highly Utilized Permanent Magnet Synchronous Motors for Finite-Control-Set Model Predictive Control - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Untersuchung von Gefahrensituationen bei industriellen Absorption/Desorption-Prozessen mittels dynamischer Simulation - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y.

Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Approximation and Online Algorithms)

Adjustment of AgCaLa Phases in a FeMn Matrix via LBM for Implants with Adapted Degradation - Krüger, Jan Tobias (crystals)

Atar-Gull o Una venganza africana de Lucio V. Mansilla: un drama del romanticismo transatlántico - Schlieper, Hendrik (El drama histórico en los romanticismos de España e lberoamérica. Procesos transnacionales de intercambio y renegociación de identidades. (Teoría y Práctica del Teatro, 29))

Knoten/Schreiben: Graffignys Lettres d’une Péruvienne und die transatlantische Schrift-Kultur-Debatte - Schlieper, Hendrik (Transatlantische Aufklärung. Erfahrungen von Identität und Alterität im 18. Jahrhundert)

The ‚Empire‘ Writes Back: Literarische Rekolonialisierungen im Frankreich des 18. Jahrhunderts (Prévost, Lesage, Fuzelier/Rameau) - Schlieper, Hendrik (200 Jahre Nationalphilologien. Von der Romantik zur Globalisierung)

Transatlantische Aufklärung. Einleitende Überlegungen - Schlieper, Hendrik; Roselli, Antonio (Transatlantische Aufklärung. Erfahrungen von Identität und Alterität im 18. Jahrhundert)

Im Namen des Vaters. Liebe, Sexualität und Familie in Carlo Goldonis "La locandiera" und Gotthold Ephraim Lessings "Emilia Galotti“ - Steigerwald, Jörn (Artes. Zeitschrift für Literatur und Künste der frühmodernen Welt, 1 / 1)

Transatlantische Aufklärung. Erfahrungen von Identität und Alterität im 18. Jahrhundert

Piezoelectric Ultrasonic Power Transducers - Hemsel, Tobias; Twiefel, Jens (Reference Module in Materials Science and Materials Engineering)
This article is dedicated to piezoelectric ultrasonic power transducers that differ to well known medical ultrasonic diagnostic apparatus or non destructive testing devices by the level of power in use; typically several tens of up to more than thousand watts are used in a multitude of different applications. After a short introduction including historical development, the first focus is on theoretical background of the operating principle, design and mechanical modeling. As piezoelectric elements transform electrical to mechanical energy and vice versa, equivalent circuit modeling is also described. After that, sample applications are delineated by the matter wherein ultrasound generates unique effects: incredible high pressure level as well in air as in water, micro-bubbles generating temperature peaks for very short time instances in fluids, acoustoplastic effect, enhancement of diffusion and recrystallization in solids, friction manipulation, incremental deformation and micro-cracking of surfaces, or even generation of macroscopic movements in motors. At the end, some future directions ranging from novel modeling approaches to advanced control and new materials are addressed.
Keywords: Equivalent circuit model; Langevin transducer; Lumped parameter model; Piezoelectric transducer; Ultrasonic processes; Ultrasound

Handlungsfelder für die KI-Einführung in der Arbeitswelt produzierender Unternehmen - Gabriel, Stefan; Aring, Theresa; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Tagungsband des 68. Frühjahrskongress der Gesellschaft für Arbeitswissenschaft)

Pattern based engineering of System of Systems - a systematic literature review - Anacker, Harald; Günther, Matthias; Wyrwich, Fabian; Dumitrescu, Roman (17th Annual System of Systems Engineering Conference (SOSE))

Identification of stakeholder-specific Systems Engineering competencies for industry - Anacker, Harald; Dumitrescu, Roman; Könemann, Ulf; Wilke, Daria (Proceedings of the 16th Annual IEEE International Systems Conference)

Himmlische Klänge und Zaubergesänge in Torquato Tassos "Gerusalemme liberata“ - Steigerwald, Jörn (Literatur und Musik im Cinquecento: Zwischen septem artes liberales und Humanismus in Italien)

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))
In this work, methods will be evaluated to numerically calculate the passive electrical parameters of planar coils. These parameters can then be used to optimize inductive applications such as wireless power transmission. The focus here will be on inductive localization, which uses high-frequency magnetic fields and the resulting induced voltage to provide localization through the coupling parameter mutual inductance. To achieve localization with high accuracy and best possible operation (resonance, signal strength, etc.), the coil parameters need to be well known. For this reason, some numerical methods for the calculation of these quantities are presented and validated. In addition, the physical effects are thereby considered in more detail, allowing the localization procedure to be better optimized compared to simulative black-box methods. The goal should be a dedicated simulation platform for planar coils to be able to develop training data for neural networks and to test and optimize localization algorithms.
Keywords: Simulation Environment; Inductive Localization; Coil Parameters; Inductive Applications; Near-Field

Detection of Defects on Irregularly Structured Surfaces using Supervised and Semi-Supervised Learning Methods - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneiß, Volker; Hedayat, Christian; Kuhn, Harald (2022 Smart Systems Integration (SSI))
In the manufacture of real wood products, defects can quickly occur during the production process. To quickly sort out these defects, a system is needed that finds damage in the irregularly structured surfaces of the product. The difficulty in this task is that each surface is visually different and no standard defects can be defined. Thus, damage detection using correlation does not work, so this paper will test different machine learning methods. To evaluate different machine learning methods, a data set is needed. For this reason, the available samples were recorded manually using a static fixed camera. Subsequently, the images were divided into sub-images, which resulted in a relatively small data set. Next, a convolutional neural network (CNN) was constructed to classify the images. However, this approach did not lead to a generalized solution, so the dataset was hashed using the a- and pHash. These hash values were then trained with a fully supervised system that will later serve as a reference model, in the semi-supervised learning procedures. To improve the supervised model and not have to label every data point, semi-supervised learning methods are used in the following. For this purpose, the CEAL method (wrapper method) is considered in the first and then the Π-Model (intrinsically semi-supervised).
Keywords: Machine Learning; CNN; Hashing; semi-supervised learning

Development of an innovative separation unit for nitrogen recovery from agricultural waste - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny
Keywords: CFD; simulation; agricultural waste; multiphase

Projektmanagement und Vorgehensmodelle 2022. Virtuelle Zusammenarbeit und verlorene Kulturen? - Fazal-Baqaie, Masud; Linssen, Oliver; Volland, Alexander; Yigitbas, Enes; Engstler, Martin; Bertram, Martin; Kalenborn, Axel

Maßnahmen zur Reduzierung von plastischer Verformung an statischen Druckplatten von Lammellenbremsen infolge einseitig eingebrachter hoher Reibleistung - Schadomsky, Magnus; Blumenthal, Lars Martin; Zimmer, Detmar; Peter, Simon; Boros, Laszlo (Forschung im Ingenieurwesen)
Die thermisch verursachte, plastische Verformung an statischen Druckplatten von Lamellenbremsen kann das Betriebsverhalten von Bremsen nachhaltig stören und sollte daher vermieden werden. So kann die plastische Verformung der Druckplatte beispielsweise zu einer Verkleinerung des Luftspalts führen und ungewollte Veränderung der Reibverhältnisse verursachen. Während des Bremsvorgangs dehnen sich hoch erwärmte Bereiche nah der Reibfläche aus und werden von den Zonen geringerer Temperatur an ihrer Ausdehnung gehindert. Überschreiten die daraus resultierenden Spannungen die Dehngrenze des Materials, kommt es zu plastischer Verformung. Dieser Artikel erläutert den physikalischen Verformungsprozess detailliert und darauf aufbauend, welche Maßnahmen zu einer Verringerung der Verformung ergriffen werden können. Dazu werden im Rahmen theoretischer Vorüberlegungen drei Ansätze identifiziert, die sowohl die Geometrie als auch die Werkstoffe der Druckplatten betreffen. Radiale Schlitze sollen die Behinderung der thermischen Dehnung verhindern und dadurch Spannungen reduzieren; die Werkstoffauswahl auf Basis der Thermoschockempfindlichkeit reduziert die plastische Verformung. Anhand einer kombinierten Simulation der Thermik und der Mechanik einer Druckplatte wird der Effekt dieser Ansätze an vier Varianten der Druckplatte überprüft. Experimentelle Untersuchungen an realen Prototypen der Druckplattenvarianten bestätigen die Ergebnisse der Simulation und weisen die Wirksamkeit der vorgeschlagenen Maßnahmen zur Reduzierung der plastischen Verformung nach.
Keywords: General Engineering; Bremsen; Bremsscheiben; thermoplastische Verformung